2004
DOI: 10.1111/j.1398-9995.2004.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase gene polymorphism and IgE‐mediated allergy in the Central European population

Abstract: Our findings suggest that NOS1 gene may participate in the pathogenesis of high total serum IgE levels in allergic diseases in our population. These findings provide support for NOS1 as a candidate gene for IgE-mediated allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…In a recent study we observed a significant interaction between eNOS-786C/T variant and gender [25]. Previously, our group studied polymorphic markers in nNOS (C5266T) and iNOS (several variants mainly in promoter region) genes and reported significant associations between the nNOS variant and plasma IgE [41], similar to that between iNOS haplotypes and asthma [42]. However, this study also has several strengths.…”
Section: Discussionmentioning
confidence: 55%
“…In a recent study we observed a significant interaction between eNOS-786C/T variant and gender [25]. Previously, our group studied polymorphic markers in nNOS (C5266T) and iNOS (several variants mainly in promoter region) genes and reported significant associations between the nNOS variant and plasma IgE [41], similar to that between iNOS haplotypes and asthma [42]. However, this study also has several strengths.…”
Section: Discussionmentioning
confidence: 55%
“…NOS1 gene, by means of the C5266T SNP, has also been associated with total IgE levels in Caucasian and Chinese populations [13, 29, 30]. Furthermore, in Chinese subjects this polymorphism was also associated with specific IgE to D. pteronyssinus, as detected by skin test [13].…”
Section: Discussionmentioning
confidence: 99%
“…NOS1 polymorphisms have been associated with asthma [9, 27, 28], IgE levels [13,29,30,31] and exhaled NO concentration [32]. The three studies showing association with asthma were performed in Caucasian and Japanese populations, two of them with the NOS1 intron 2 CA repeat and the other with the exon 29 CA repeat.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been reported that SNPs in NOS1 are associated with asthma, eosinophil counts and total serum IgE levels [13 ]. Holla, et al [48] confirmed that SNPs in NOS1 are associated with IgE-mediated allergy in a Central European population [48].…”
Section: Chromosome 12q Regionmentioning
confidence: 84%